2003
DOI: 10.1021/ja029840z
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Study of the 13C and 31P Chemical Shielding Tensors in Solid O-Phosphorylated Amino Acids

Abstract: A series of l and dl forms of O-phosphorylated amino acids (serine, threonine, tyrosine) have been studied by using solid-state multinuclear NMR spectroscopy and ab initio calculations. Principal elements of the (13)C and (31)P chemical shielding tensors have been measured and discussed in relation to zwitterionic structures and intermolecular contacts. DFT calculations have been compared with experimental data showing their ability to reproduce experimentally obtained tensor values in this challenging class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 57 publications
11
70
3
Order By: Relevance
“…The most intense peak, at 1 H 4.5 ppm, is assigned to pSer methylene β1,2 protons, since its chemical shift corresponds to previously reported values 5 and its correspondent H bond distances. 20,21,22 This signal comes necessarily from the strong interaction between the proton and organic phosphorous in phosphoserine. An interaction between pSer methylene β1,2 protons and the 31 P from ACP is unlikely since, the average distance between phosphoserine Hβ and inorganic phosphorous is too great to generate a signal in CP (between 7-9 Å).…”
Section: Proton Proton Protonmentioning
confidence: 99%
See 1 more Smart Citation
“…The most intense peak, at 1 H 4.5 ppm, is assigned to pSer methylene β1,2 protons, since its chemical shift corresponds to previously reported values 5 and its correspondent H bond distances. 20,21,22 This signal comes necessarily from the strong interaction between the proton and organic phosphorous in phosphoserine. An interaction between pSer methylene β1,2 protons and the 31 P from ACP is unlikely since, the average distance between phosphoserine Hβ and inorganic phosphorous is too great to generate a signal in CP (between 7-9 Å).…”
Section: Proton Proton Protonmentioning
confidence: 99%
“…an average change in H-bond of only 0.05 Å induces a shift of more than 2 ppm). 14,22 As a consequence, the increase in the dipolar signal necessarily reflects the increase in the percentage (+33%) of 4-The impact of temperature: The increase in concentration competes with the destabilizing effect of temperature.…”
Section: Proton Proton Protonmentioning
confidence: 99%
“…As such, the authors achieved a much better agreement between the theoretical values and experimental results. In an earlier study, 27 we also performed calculations by combining a supramolecular model 18 with ONIOM method 5,28 to investigate the effects of electrostatic interactions and intermolecular hydrogen bonding on the shielding tensors of amino acids. The results led us to the conclusion that the shielding tensors of carboxyl carbons are readily sensitive to the short-range interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade research based on an approach of combined computational and solid-state NMR methodology showed that there is a close relation between NMR tensors and structure. [10][11][12][13][14][15] This correlation has been used to investigate structural features like for example configuration, [16][17][18][19][20] hydrogen bonding [21,22] or even intermolecular arrangement [23] in the solid state. For a description of the tensor in condensed phases the polarizable continuum model, [24,25] embedded cluster methods [22,24] and computations under full periodic boundary conditions using plane waves [26][27][28][29] have been used most recently.…”
Section: Introductionmentioning
confidence: 99%